2014
DOI: 10.1111/iej.12390
|View full text |Cite
|
Sign up to set email alerts
|

CBCT‐based volume of simulated root resorption – influence of FOV and voxel size

Abstract: Despite the FOV protocol, voxel size can influence measurement of simulated IRR volumes. The importance of standardization of CBCT image acquisition protocols is emphasized, especially during follow-up of an IRR lesion, to prevent misinterpretation of its extent, which can create a bias in clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
22
1
3
Order By: Relevance
“…Finally, the diagnostic accuracy of CBCT for external root resorption at different voxel sizes was also examined by Neves et al; in which an increase in cavity size yielded higher values for diagnostic accuracy, PPV and NPV [22,24,25]. This study, however, showed that overall the voxel size used in the current study for CBCT images had no statistically significant effect on the diagnostic accuracy of large and small images at the different levels of the root.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Finally, the diagnostic accuracy of CBCT for external root resorption at different voxel sizes was also examined by Neves et al; in which an increase in cavity size yielded higher values for diagnostic accuracy, PPV and NPV [22,24,25]. This study, however, showed that overall the voxel size used in the current study for CBCT images had no statistically significant effect on the diagnostic accuracy of large and small images at the different levels of the root.…”
Section: Discussionmentioning
confidence: 61%
“…Goldberg et al; examined the ability of CBCT in detecting simulated external root resorption in the incisor teeth of upper jaw and concluded that the detection of small cavities, compared to cavities of intermediate and large sizes, is laborious and difficult [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…Upon dissociation CH produces high pH (12.5-12.8) preventing the dissolution of mineral components of dentin, in addition to activating alkaline phosphatase, which plays an important role in the formation of hard tissue [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, diagnosis by CBCT may improve the accuracy and efficiency in the prognosis of the tooth 14,15 . The purpose of this case report is to describe the diagnosis and clinical management of an internal root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…when evaluating airway estimation tools, as well as the phantom utilized. [7][8][9][10][11] For cephalometric and airway analysis, a large field of view (FOV) is frequently chosen to include all regions of interest. Usually, bigger voxel sizes are selected for large FOV's because it requires less scan and reconstruction time, and therefore less radiation for the patient; however, larger voxel sizes reduce spatial resolution.…”
mentioning
confidence: 99%